Southern Europe perspectives on international student mobility - Malet Calvo, D.; Cairns, D.; França, T. (Portuguese Journal of Social Science, 2020)
During the last four decades, higher education institutions (hereafter, HEIs) have experienced an unprecedented level of internationalization, closely linked to pressures induced by economic globalization (Kehm and Teichler 2007). The dominance of post-industrial capitalism, a revolution brought about by new information technologies and the postcolonial scenario of emerging countries demanding access to higher education are at the core of a worldwide engagement with internationalization (Lumby and Foskett 2016). The demand for status-generating tertiary education from middle class and elite families in countries such as China, India, South Korea, Brazil and Nigeria has stimulated the struggle between nations that seek to dominate the global education market (Waters and Leung 2013). The most prominent universities in the United States, United Kingdom, Australia, Canada and Germany have begun offering distance education courses, joint programmes and academic partnerships, opening campus branches overseas and, of course, recruiting as many mobile students as possible (Walker 2014). In this sense, internationalization might rather be labelled ‘transnationalization’ as its principal feature is not the expansion of HEIs on an international scale but rather the commercialization of educational goods and services worldwide (Verger et al. 2016). In fact, educational goods are now included in the General Agreement on Trade in Services (GATS) of the World Trade Organization (WTO).